A Systematic Literature Review on The Use of MALL (Mobile-Assisted Language Learning) in English Learning and Teaching Process Across Educational Levels in Indonesia - Niya Erawati; Nunung Suryati; Ekaning Dewanti Laksmi; Suhono, Suhono; Risky Ba’da Mauludiyah (Yayasan Payungi Smart Madani, 2025)
MALL (Mobile-Assisted Language Learning) in educational settings has become increasingly widespread. Particularly in the English learning and teaching process. There are various studies investigating MALL which is believed to help improve language learning and teaching process. This paper systematically explored the use of MALL in English learning and teaching processes across educational levels in Indonesia based on empirical studies. Forty-five articles were selected from reputable journals, reviewed to identify the pedagogical approaches offered by MALL to know the potential mobile device tools that could be used in the English learning and teaching process. The findings have shown a steady increase in research on the use of MALL across educational levels in Indonesia. However, the need for improvement studies employs the mixed-method approach, qualitative and quantitative for future studies. In addition, further investigation is also required to assess the efficiency of MALL in enhancing English skills. In order to understand how MALL promotes multimodal material, learners’ autonomy, incorporates real, and increases students’ engagement through gamification, this study synthesizes current empirical data with an emphasis on the Indonesian context. This study offers a contextualized understanding of pedagogical techniques pertinent and mobile learning tools to Indonesian Education levels. In contrast to other reviews that concentrated on specialize ability or more general global viewpoints. To sum up, future research should focus on the thoughtful integration of MALL, pedagogical approach, and the potential mobile device tools that can be used to yield more meaningful outcomes